Potensi Antibakteri Ekstrak Spons Laut Koleksi Perairan Grand Watu Dodol Banyuwangi - Dian Sari Maisaroh; Nor Sa'adah; Yahya Abdillah Al Hanif (JURNAL PERIKANAN DAN KELAUTAN, 2023)
This study aims to the antibacterial activity of sea sponge extract from the waters of Grand Watu Dodol Banyuwangi against the pathogenic bacteria Staphylococcus aureus, Vibrio parahaemolyticus, Escherichia coli and Escherichia coli MDR (Multi Drug Resistant). This study uses an experimental laboratory method. The samples found were 3 sponges and macerated using methanol solvent with 3 repetitions. The results of the sponge extract paste were tested by disc diffusion method against pathogenic bacteria S. aureus, V. parahaemolyticus, E. coli and E. coli MDR. Antibacterial test using a concentration of 10 mg/ml with 2 repetitions. The extraction results obtained from the four samples only 3 that can produce bioactive compound extracts. Antibacterial activity against pathogenic bacteria S. aureus produced the largest inhibition zone obtained by GWD B with an average of 8.89 mm. Pathogen E.coli, the largest inhibition zone obtained by GWD B with an average of 8.90 mm. Pathogen V. parahaemolyticus the largest inhibition zone obtained by GWD A produced an inhibition zone with an average of 7.30 mm. Pathogen E.coli MDR produced the largest inhibition zone obtained by GWD A with the largest average inhibition zone of 7.26 mm.